2020
DOI: 10.7554/elife.52859
|View full text |Cite
|
Sign up to set email alerts
|

Phrenic-specific transcriptional programs shape respiratory motor output

Abstract: The precise pattern of motor neuron (MN) activation is essential for the execution of motor actions; however, the molecular mechanisms that give rise to specific patterns of MN activity are largely unknown. Phrenic MNs integrate multiple inputs to mediate inspiratory activity during breathing and are constrained to fire in a pattern that drives efficient diaphragm contraction. We show that Hox5 transcription factors shape phrenic MN output by connecting phrenic MNs to inhibitory premotor neurons. Hox5 genes es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(48 citation statements)
references
References 50 publications
1
47
0
Order By: Relevance
“…In addition, N MNΔ and N MNΔ 6910 -/- mice showed a similar decrease in phrenic MN numbers, likely from the loss of trophic support due to the decrease in diaphragm innervation (Figure S3c). While phrenic MN loss may contribute to the perinatal lethality observed in N MNΔ 6910 -/- mice, we have previously found that, even after substantial MN loss, 50% of surviving phrenic MNs are sufficient to support life (Vagnozzi et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, N MNΔ and N MNΔ 6910 -/- mice showed a similar decrease in phrenic MN numbers, likely from the loss of trophic support due to the decrease in diaphragm innervation (Figure S3c). While phrenic MN loss may contribute to the perinatal lethality observed in N MNΔ 6910 -/- mice, we have previously found that, even after substantial MN loss, 50% of surviving phrenic MNs are sufficient to support life (Vagnozzi et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1. A combinatorial cadherin code establishes breathing and is required for life a) A combinatorial cadherin code defines phrenic MNs during development (adapted from Vagnozzi et al, 2020). b) To determine the function of cadherins in respiratory motor circuits, we specifically inactivated a combination of type I and type II cadherins in MNs-N-cadherin and Cadherins 6, 9, 10 (N-cad flox/flox;Olig2-Cre;Cdh6/9/10-/-, referred to as N MNΔ 6910 -/mice).…”
Section: Figure Legendsmentioning
confidence: 99%
“…In addition, we found differences among the two datasets that, in part, might highlight the different ages sampled. For example, we found that unlike adult mouse αMNs, human PCW17-18 αMNs expressed several type II cadherins ( CDH7, CDH9, CDH10 , CDH20 ) that might regulate motor pool segregation (Dewitz et al, 2019; Price et al, 2002; Vagnozzi et al, 2020). Other differences included the expression of UNC5B, TXK and DGKK in human αMNs, and the expression of NDNF , CLIC5 and GFRA2 in human γMNs.…”
Section: Resultsmentioning
confidence: 98%
“…In spinal cord circuits, several studies revealed connectivity defects upon Hox gene inactivation (Dasen et al, 2005(Dasen et al, , 2008Catela et al, 2015Catela et al, , 2016Baek et al, 2019). For example, Hox5 genes are required for proper connectivity of phrenic motor neurons to premotor interneurons and the diaphragm muscle (Philippidou et al, 2012;Vagnozzi et al, 2020). The phrenic motor neurons express a unique combination Hox5-dependent cell adhesion molecules of the Cadherin (Cdh) family (Vagnozzi et al, 2020), which is known to control neuronal connectivity across model systems.…”
Section: Control Of Synapse Formation/maturation By Mouse Hox Genesmentioning
confidence: 99%
“…For example, Hox5 genes are required for proper connectivity of phrenic motor neurons to premotor interneurons and the diaphragm muscle (Philippidou et al, 2012;Vagnozzi et al, 2020). The phrenic motor neurons express a unique combination Hox5-dependent cell adhesion molecules of the Cadherin (Cdh) family (Vagnozzi et al, 2020), which is known to control neuronal connectivity across model systems. Importantly, early or late genetic removal of Hox5 in mice affects diaphragm innervation, suggesting a continuous Hox requirement for establishment and maintenance of neuronal wiring (Philippidou et al, 2012).…”
Section: Control Of Synapse Formation/maturation By Mouse Hox Genesmentioning
confidence: 99%